Lecturer's Online Instructional Strategies in English Speaking Class during COVID-19 Pandemic Period at IAIN Palopo, South Sulawesi - Nirmala Sudarti (Institut Agama Islam Negeri Palopo, 2022)
The study aimed to find out the types of online instructional strategies, Lecturer’s perception, how to conduct online speaking class, the impact of online instructional strategies on students speaking activity and Lecturer’s online instructional strategies implementation. The research was conducted through qualitative research with descriptive analysis at IAIN Palopo. The result revealed that direct instruction, indirect instruction, ADDIE Model and Mahmood’s strategy were the types of online instructional strategies were applied in English speaking class, meanwhile, Lecturer’s perception were classified into three aspects: place of origin of the students, poverty issues, and students’ attitude toward online learning. To conduct English speaking class Lecturer utilized online learning platform. The findings revealed there were seven students faced technical problems on online learning, and it was contrasting with other thirteen students. Poverty issues, internet connectivity, neglected area, limitation time, lack of infrastructural development and lack of students’ motivation were technical problems which impacted online learning on English speaking class at IAIN Palopo.